DEFINITION OF THE CONCEPT OF "CULTURE" AND ITS SCIENTIFIC FOUNDATIONS - Ibodulla Kungirov (Journals Park Publishing, 2023)
In this article, the emergence of the concept of culture, the definitions given by different scientists in different periods are analytically described on a scientific basis. In addition, special attention is paid to the perception of culture as a phenomenon, the importance of laws that directly affect its development, and issues related to the management of culture based on them. The theoretical foundations of the term "culture" are objectively approached and corresponding scientific and creative conclusions are given.
Keywords: Culture, civilization, technology, science, art, political institutions, history, cultural life, art, ethics, antiquity, traditions, cultural studies.